Web application security analysis using the Kali Linux operating system - Babincev, Ivan M.; Vuletić, Dejan V. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The Kali Linux operating system is described as well as its purpose and possibilities. There are listed groups of tools that Kali Linux has together with the methods of their functioning, as well as a possibility to install and use tools that are not an integral part of Kali. The final part shows a practical testing of web applications using the tools from the Kali Linux operating system. The paper thus shows a part of the posibilities of this operating system in analysing web applications security, which presents the goal of this work.
Keywords: security; web application; Kali Linux